Job Demands, Job Resources, and Job Performance in Japanese Workers: A Cross-sectional Study - NAKAGAWA, Yuko (National Institute of Occupational Safety and Health, Japan, 2014)
This study investigated the cross-sectional association of job demands (i.e., psychological demands) and job resources (i.e., decision latitude, supervisor support, co-worker support, and extrinsic reward) with job performance. A total of 1,198 workers (458 males and 740 females) from a manufacturing company in Japan completed a self-administered questionnaire that included the Job Content Questionnaire, Effort-Reward Imbalance Questionnaire, World Health Organization Health and Work Performance Questionnaire, and demographic survey. Hierarchical multiple regression analyses were conducted. After adjusting for demographic characteristics, decision latitude (β=0.107, p=0.001) and extrinsic reward (β=0.158, p<0.001) were positively and significantly associated with job performance while supervisor support (β=−0.102, p=0.002) was negatively and significantly associated with job performance. On the other hand, psychological demands or co-worker support was not significantly associated with job performance. These findings suggest that higher decision latitude and extrinsic reward enhance job performance among Japanese employees.